EFFECT OF THE ISOMETRIC - ISOTONIC EXERCISE ON LIGAMENTS RUPTURE INJURY OF KNEE AND REHABILITATION FOR ATHLETIC - Waleed Adnan; Rusu Ligia; Ali Bediwy (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2021)
Introduction.Rehabilitation is a program of treatment with some sport exercises targeting the lower body .The aim:of the study is to develop the work of the knee joint after the ligament rupture injury and to rehabilitate itby preparation of the (PTP) proposed training program.Material and Method:The study included 4 injured athletes who were selected from a total of 10 injured.The tools used to measure the angle of flexion and extension of the knee joint before and after rehabilitation are tape measure , anthropometric measurements and squat equipment. Statistical analyses:which used included MEAN, STD, MAX, MIN, MEDIAN to explain the results. Anthropometricis used to measure the (TCUIL) Thigh circumference of upper injured limb and (CBIL) Circumference of bottom injured, Flexion and extension angle of the knee joint and isometric -isotonic exercises with Pre-test -post-test for 4 injures athletes. Results :using the intensity of 30-35% until it reached 95-100% after the end of the training program with 9 -10Kg weights in the first week until 30-35 Kg on squat equipment at the end of the fourth week and it was cured and Anthropometrics of Pre-test was (TCUIL) was 49 and Post-test was 50 cm with increase1cmand the Pre-test of (CBIL) was 34.5 and Post-test 34.7 cm with increase(0.2mm).Conclusions:: The (PTP) developed muscle strength of the femoral muscle groups working on the knee joint after used isometric isotonic exercise